2017
DOI: 10.1142/s0192415x17500744
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: Herbal Medicine Treatment after Large-Scale Disasters

Abstract: Large-scale natural disasters, such as earthquakes, tsunamis, volcanic eruptions, and typhoons, occur worldwide. After the Great East Japan earthquake and tsunami, our medical support operation's experiences suggested that traditional medicine might be useful for treating the various symptoms of the survivors. However, little information is available regarding herbal medicine treatment in such situations. Considering that further disasters will occur, we performed a literature review and summarized the traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
“…Earthquakes, like any other disasters, are traumatic events and they result in a range of physical, mental and psychological health consequences [2,8,[12][13][14][15]43,[50][51][52]56]. Indeed, this is attested to in the results of six studies in our systematic review [35][36][37][38][39]41]-which showed a high prevalence of PTSD among the different groups of survivors of the 2008 Wenchuan earthquake.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations